[5 is the problem number. Do not multiply your answer by 5.]
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
nice solution...! did the same way
awesome dude!
By using this fact,
i ( i + 1 ) 1 = i 1 − i + 1 1
we could compute that the denominator's value would become 1 − 1 0 1 1 = 1 0 1 1 0 0 .
Which lead us to ( 1 0 1 1 0 0 ) 1 = 1 0 0 1 0 1 = 1 . 0 1 as the solution of the problem.
Problem Loading...
Note Loading...
Set Loading...
Note that
i = 1 ∑ 1 0 0 i ( i + 1 ) 1 = 1 ( 2 ) 1 + 2 ( 3 ) 1 + ⋯ + 9 9 ( 1 0 0 ) 1 + 1 0 0 ( 1 0 1 ) 1
Since
i ( i + 1 ) 1 = i 1 − i + 1 1
1 ( 2 ) 1 + 2 ( 3 ) 1 + ⋯ + 9 9 ( 1 0 0 ) 1 + 1 0 0 ( 1 0 1 ) 1
= 1 1 − 2 1 + 2 1 − 3 1 ⋯ + 9 9 1 − 1 0 0 1 + 1 0 0 1 − 1 0 1 1
= 1 1 − 1 0 1 1
= 1 0 1 1 0 0
Hence the desired answer is 1 0 1 1 0 0 1 = 1 0 0 1 0 1 = 1 . 0 1 .